Analysis of mathematical reasoning ability of junior high school students of grade VII viewed from cognitive style on problem based learning with mind mapping - Mardiyah, Istianatun; Suhito, Suhito; Safa'atullah, Muhammad Fajar (Department of Mathematics, Universitas Negeri Semarang, 2018)
The method used in this research is a mixed method with the research design that is explanatory sequential design. The result of this research are (1) Mathematical reasoning ability of grade VII students after being given learning by using PBL with mind mapping reached minimal completeness criteria; (2) the description of students' mathematical reasoning ability with independent field cognitive style were capable to present mathematical statements, propose conjecture, do mathematical manipulation, give reason to solution, and draw conclusion; and (3) the description of students' mathematical reasoning ability with field-dependent cognitive style were capable to present mathematical statements, yet incapable to propose conjecture, FDK students were less able to manipulate mathematics, while FDL students were incapable to perform mathematical manipulation, provide reason for solution, and draw conclusions.